Analisis Anggaran Pendapatan dan Anggaran Biaya Sebagai Evaluasi Dalam Pencapaian Sisa Hasil Usaha (SHU) di PKPRI Pamekasan - Moh. Herman Djaja; Zainal Mahfud; Rio Hendra Cahyadi (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
The center of Indonesian Employees Cooperative (PKPRI) is one of the cooperatives in Pamekasan regency which formed in the year 1960. Every year PKPRI make budget income and expenses and business run PKPRI is crediting, leasing, hospitality, USP GKPRI Jatim. But in the restoration of the remainder of the business results PKPRI can not stabilize the SHU received annually. As the year 2016 is very unstable, it reaches a decrease of 50% from the previous year. The purpose of this research is to know how budgets are made in the evaluation of SHU's achievement. This method of research is a quantitative and qualitative descriptive with static comparative analysis techniques. Data is collected with documentation and interview techniques. Analysis results showed that in making budget and evaluation in the achievement of SHU is still less good, such as two years showed from what is budgeted in terms of revenue did not experience, so that there is no stabilization in the achievement of SHU not even achieved. It is hoped that the management of cooperatives in conducting income budgeting and costs involve stakeholders and is more involved in promotion so that what is estimated in terms of revenue can be achieved and stable.Keyword: Budget income; cost; SHU